Effect of pre-sowing treatments on germination, growth and vigour attributes of white sapote (Casimiroa edulis) - M, MURALIDHARA B; S, RAJENDIRAN; S, MADHU G; T, RANI A; D, DEEKSHITH; M, MITHUN P (The Indian Journal of Agricultural Sciences, 2023)
White sapote is an exotic fruit crop gaining popularity at present days due to the occurrence of high medicinal value. The present experiment was carried out under polyhouse conditions at Central Horticultural Experiment Station, Chettalli, Kodagu, Karnataka during 2022 with an objective to know the effect of pre-sowing treatments on germination and growth attributes of white sapote. The experimental results revealed that the initiation of germination and complete germination was faster in seed coat removal treatment and KNO3 0.5% treated seeds as compared to control. The high germination per cent was also reported in seed coat removal followed by KNO3 0.5% and minimum was noticed in GA3 200 ppm which was on par with KNO3 1% and control. The seedling growth and vigour traits were also found superior in seed coat removal compare to other treatments. The correlation studies showed that, the initiation of germination had positive correlation with days taken for 50% and complete germination and negative correlation with other plant characters. In conclusion, the seed coat removal and soaking of seeds in KNO3 0.5% improves seed germination seedling vigour which helps in attaining early grafting stage.